Research on the Performance Optimization of Turbulent Self-Noise Suppression and Sound Transmission of Acoustic Windows Made from Functionally Graded Material - Bing LI; Fu-Lin ZHOU; Jun FAN; Bin WANG; Liwen TAN (Archives of Acoustics)
For a simplified sonar dome model, an optimization method for internal gradients of functionally graded material (FGM) acoustic windows is proposed in this paper. This method can be used to design optimized FGM acoustic windows with better turbulent self-noise suppression and sound transmission performances. A theoretical model of FGM acoustic windows to evaluate the reduction of self-noise caused by the turbulent boundary layer (TBL) pulsating pressure and the sound transmission loss (STL) is derived through the double Fourier transform and the wavenumber frequency spectrum analysis, respectively, based on the transfer matrix idea and the classical elastic theory. The accuracy of the theory is verified by the finite element results of COMSOL Multiphysics. Utilizing the genetic algorithm (GA) and taking the monotonic gradient as the constraint condition, the internal gradient optimization method of FGM acoustic windows obtains the optimization variables in the Bernstein polynomial when the optimization objective is minimized by iterating the optimization variables in the deviation function represented by the Bernstein polynomial that is introduced in the gradient function. The STL, the turbulent self-noise reduction or a weighting function of the STL and turbulent self-noise reduction of FGM acoustic windows is chosen as the optimization objective. The optimization calculation of the sound transmission or turbulent self-noise suppression performances is carried out for the FRP-rubber FGM (FGM with fiber reinforced plastic (FRP) as the substrate material and rubber as the top material) acoustic window. The optimized results show that both the sound transmission and turbulent self-noise suppression performance are effectively improved, which verifies the effectiveness of the optimization method. Finally, the mechanism of the sound transmission and self-noise suppression characteristics before and after optimization are explained and analyzed based on the equivalent model of graded materials. The research results of this paper provide a reference value for the future design of FGM acoustic windows for sonar domes.